2020
DOI: 10.1074/jbc.ra120.015552
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-specific deletion of the transcription factor Yin Yang 1 in murine substantia nigra mitigates manganese-induced dopaminergic neurotoxicity

Abstract: Manganese (Mn)-induced neurotoxicity resembles Parkinson’s disease (PD), but the mechanisms underpinning its effects remain unknown. Mn dysregulates astrocytic glutamate transporters, GLT-1 and GLAST, and dopaminergic function, including tyrosine hydroxylase (TH). Our previous in vitro studies have shown that Mn repressed GLAST and GLT-1 via activation of transcription factor Yin Yang 1 (YY1). Here, we investigated if in vivo astrocytic YY1 deletion mitigates Mn-induced dopaminergic neurotoxicity, attenuating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 96 publications
2
53
0
Order By: Relevance
“…Mn exposure (30 mg/kg intranasal for 21 days) was shown to decrease EAAT1 (GLAST) and EAAT2 (GLT-1) promotor activities, as well as mRNA and protein levels resulting in reduced glutamate uptake in human astrocyte H4 cells as well as murine brain, being associated with neurobehavioral deficiency, reduced tyrosine hydroxylase mRNA and protein levels, as well as reduced histone H3 and H4 acetylation [ 171 ], all being reversed by valproic acid and sodium butyrate [ 172 ]. Our previous data from both in vitro (exposure to 250 μM Mn for 6 h) [ 173 , 174 ] and in vivo (exposure to 30 mg/kg intranasal for 21 days) [ 175 ] studies demonstrate that activation of Yin Yang 1 (YY1) transcription factor plays a significant role in GLAST and GLT-1 expression, whereas YY1 knockout significantly attenuated Mn-induced motor dysfunction, glutamate transporter reduction, tyrosine hydroxylase activity, as well as histone deacetylation [ 176 ]. At the same time, it has been demonstrated that a time- and dose-dependent increase in GLAST activity in chick cerebellar Bergmann glia cells in response to acute but non-toxic Mn exposure (200 µM for 30 min) may be associated with increased transporter affinity for [ 3 H]-d-aspartate [ 177 ].…”
Section: Neurotransmissionmentioning
confidence: 99%
“…Mn exposure (30 mg/kg intranasal for 21 days) was shown to decrease EAAT1 (GLAST) and EAAT2 (GLT-1) promotor activities, as well as mRNA and protein levels resulting in reduced glutamate uptake in human astrocyte H4 cells as well as murine brain, being associated with neurobehavioral deficiency, reduced tyrosine hydroxylase mRNA and protein levels, as well as reduced histone H3 and H4 acetylation [ 171 ], all being reversed by valproic acid and sodium butyrate [ 172 ]. Our previous data from both in vitro (exposure to 250 μM Mn for 6 h) [ 173 , 174 ] and in vivo (exposure to 30 mg/kg intranasal for 21 days) [ 175 ] studies demonstrate that activation of Yin Yang 1 (YY1) transcription factor plays a significant role in GLAST and GLT-1 expression, whereas YY1 knockout significantly attenuated Mn-induced motor dysfunction, glutamate transporter reduction, tyrosine hydroxylase activity, as well as histone deacetylation [ 176 ]. At the same time, it has been demonstrated that a time- and dose-dependent increase in GLAST activity in chick cerebellar Bergmann glia cells in response to acute but non-toxic Mn exposure (200 µM for 30 min) may be associated with increased transporter affinity for [ 3 H]-d-aspartate [ 177 ].…”
Section: Neurotransmissionmentioning
confidence: 99%
“…In addition, Mn-induced glutamate dyshomeostasis could be associated with glutamate transporter dysfunction. We have previously reported that Mn decreased the glutamate uptake in astrocytes, along with a reduced expression of glutamate aspartate transporter 1 (GLAST) and glutamate transporter 1 (GLT-1), resulting in excess extracellular glutamate levels [ 8 , 149 , 150 ]. Since GLAST and GLT-1 are predominantly expressed in astrocytes and responsible for >90% of the glutamate uptake from the extracellular space in the brain [ 145 ], this Mn-reduced GLT-1/GLAST could directly contribute to excitotoxic neuronal injury.…”
Section: Mechanisms Of Mn-induced Neurotoxicitymentioning
confidence: 99%
“…We have found that the Mn-decreased expression of GLT-1/GLAST was at the transcriptional level. The Mn-induced activation of the transcription factor Yin Yang 1 (YY1) was responsible for repressing GLAST and GLT-1 expression in both in vitro astrocyte cultures and in vivo mouse models [ 8 , 149 , 150 ]. Mn also modulated epigenetic modifier histone deacetylases (HDAC) to repress GLAST and GLT-1 expression by increasing the interaction of HDAC with YY1 and the subsequent histone deacetylation in astrocytes [ 149 , 150 ].…”
Section: Mechanisms Of Mn-induced Neurotoxicitymentioning
confidence: 99%
See 2 more Smart Citations